Anterior Approach in a Huge Lipomatous Tumor of the Thigh - Jordi Faig-Martí (Case Reports in Medicine)
Confronted with a huge lipomatous anterior thigh tumor, the surgical approach had to be assessed. Those described in the literature did not seem appropriate for our case so some modifications were made. We present the case of a 77-year-old woman who presented with a huge anterior thigh compartment tumor with one-year evolution. Magnetic resonance imaging informed the presence of a lipomatous tumor with a possible vascular contact. Based on Thomson’s anterior approach, but modifying the skin incision, the medial distal femur was reached until the neurovascular bundle and, proximally, the lesser trochanter. The tumor was totally resected due to a good visualization using this approach.